Skin Cyst: A Pathological Dead-End With a New Twist of Morphogenetic Potentials in Organoid Cultures - Qiu, Weiming; Gu, Pei-Rong; Chuong, Cheng-Ming; Lei, Mingxing (Frontiers in Cell and Developmental Biology, 2021)
A cyst is a closed sac-like structure in which cyst walls wrap certain contents typically including air, fluid, lipid, mucous, or keratin. Cyst cells can retain multipotency to regenerate complex tissue architectures, or to differentiate. Cysts can form in and outside the skin due to genetic problems, errors in embryonic development, cellular defects, chronic inflammation, infections, blockages of ducts, parasites, and injuries. Multiple types of skin cysts have been identified with different cellular origins, with a common structure including the outside cyst wall engulfs differentiated suprabasal layers and keratins. The skin cyst is usually used as a sign in pathological diagnosis. Large or surfaced skin cysts affect patients’ appearance and may cause the dysfunction or accompanying diseases of adjacent tissues. Skin cysts form as a result of the degradation of skin epithelium and appendages, retaining certain characteristics of multipotency. Surprisingly, recent organoid cultures show the formation of cyst configuration as a transient state toward more morphogenetic possibility. These results suggest, if we can learn more about the molecular circuits controlling upstream and downstream cellular events in cyst formation, we may be able to engineer stem cell cultures toward the phenotypes we wish to achieve. For pathological conditions in patients, we speculate it may also be possible to guide the cyst to differentiate or de-differentiate to generate structures more akin to normal architecture and compatible with skin homeostasis.